Redefinition of Religious Nation-state; Tracing Textual Doctrine and its Impact on Religious Violence in Indonesia - Fithriyyah, Mustiqowati Ummul; Umam, Muhammad Saiful; Astuti, Atika Windi; Alkadafi, Muammar (ADDIN, 2021)
This paper elaborates on the roots of textual indoctrination in religious violence. This study is important to redefine the concept of religious nation-state in order to avoid the distortion of religious texts’ understanding that can lead to religious violence. This research uses a literature approach. The results of this study state that 1) religious violence is divided into three, namely: internal violence of religious communities, violence between religions and forces outside of religion such as power regimes, and violence between religious communities, 2) Interpretation of religious texts are often obscured by people who want to use it as a tool to legalize violent acts. The deconstruction of the verses of the Quran against the justification of radicalism is often associated with verses describing warfare, identified with the meaning of jihad in the Way of Allah, which is contained in At-Taubat verse: 24, Al-Hajj verse: 78, Al-Mumtahanah verse: 1, Al-Ankabut verse: 6. Whereas in term of warfare stated in the Al-Baqarah verse: 190, it is clear that the only war that is permitted is only for the purpose of defense, not for offense so let alone to take innocent victims, 3) Interpretation of the meaning of truth often triggers the justification of religious violence. This is because every religion has its own scriptural doctrines which lead their believers into the belief that their religion is the most correct one. However, we must not force other believers into believing what we believe as the truth.